IMPLEMENTASI TURJUMAN DALAM MENINGKATKAN PEMAHAMAN AL-QUR’AN SISWA DI SMP IT DAARUSSALAM - Ramdan Tamara; Irham Irham (Turats, 2022)
The background of the problem in this review is about the overall obstacles that occur in turjuman learning in schools. The use of an inappropriate learning method makes students bored and lacks concentration and in the use of this method there is still a lack of supporting power provided by educational institutions. The purpose of carrying out the research is to find out the implementation of turjuman learning, its advantages and disadvantages, as well as the support and obstacles of turjuman learning at SMP IT Daarussalam. The research approach is using descriptive qualitative. The subjects used in the study were the head, deputy head, teachers and students of the turjuman class. The instrument of this research is the writer who researches directly, collects data and conducts analysis during the research process is ongoing. The results that have been obtained show that this turjuman learning applies the ummi approach with direct, repetition and sincere affection. Turjuman has three characteristics, including a more practical direct approach and the chosen teacher. Turjuman's learning is based on the ummi method of learning the Qur'an, practical media, and the teacher who teaches it. The excellence of Turjuman Ummi's learning is the type of learning that prioritizes student activity and the presence of professional teachers marked by certified teachers. Obstacles in Turjuman Ummi's learning are changes in students' vocal cords, good thinking skills to absorb material, and the lack sof learning media in the form of materials and other supporting media such as audio and video.